1991
DOI: 10.1002/ajh.2830360103
|View full text |Cite
|
Sign up to set email alerts
|

Impaired production of burst promoting activity by blood mononuclear cells from chronic uremic patients

Abstract: The ability of blood mononuclear cells (MNC) to produce burst promoting activity (BPA) was evaluated in 31 patients with chronic renal failure. The BPA of cells from uremic patients, with or without hemodialysis, was consistently lower than that of 17 normal donors (mean 64%, P less than 0.01). Coculture of MNC with recombinant erythropoietin (rEpo) in vitro did not increase BPA production. Five of 31 patients received in vivo treatment with rEpo (1,500 units x3/week) and showed therapeutic benefit, but in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…The composite nature of BPA can best explain the observation that the burst-enhancing effect derived from monocytes and stimulated T-cells [25] is distinct from that attributable to normal, unstimulated B-cells [26]. The demonstration that the mononuclear cells from patients with chronic uremia have an impaired production of BPA, irrespective of hemodialysis, conflicts with our study [27]. These authors, however, only studied T-cell and monocyte-derived BPA, raising the possibility that the stimulatory activity in our patients may have a different origin.…”
Section: Discussioncontrasting
confidence: 77%
“…The composite nature of BPA can best explain the observation that the burst-enhancing effect derived from monocytes and stimulated T-cells [25] is distinct from that attributable to normal, unstimulated B-cells [26]. The demonstration that the mononuclear cells from patients with chronic uremia have an impaired production of BPA, irrespective of hemodialysis, conflicts with our study [27]. These authors, however, only studied T-cell and monocyte-derived BPA, raising the possibility that the stimulatory activity in our patients may have a different origin.…”
Section: Discussioncontrasting
confidence: 77%
“…We previously reported that a deficiency of erythropoietin is not the sole mechanism in the development of renal anemia. We demonstrated that the burst-promoting activity (BPA) of stimulated peripheral blood mononuclear cells from uremic patients is disturbed, which may explain the occasional poor response to therapy with human recombinant erythropoietin (Epo) (2,3). We also found that the level of M-CSF before the initiation of therapy was inversely correlated with the response to subsequent Epo therapy.…”
Section: Introductionmentioning
confidence: 99%